1987
DOI: 10.4319/lo.1987.32.4.0895
|View full text |Cite
|
Sign up to set email alerts
|

In situ culturing as a test of the larval starvation hypothesis for the crown‐of‐thoms starfish, Acanthaster planci1

Abstract: In situ culturing as a test of the larval starvation hypothesis for the crown-of-thorns starfish, Acanthaster pland AbstractAs a test of the hypothesis that larvae of the crown-of-thorns starfish, Acunthaster planci, are sevcrcly food limited, larvae were reared in situ in natural seawater and in natural seawater enriched with cultured phytoplankton. Although phytoplankton levels remained below the minimum threshold needed to support A. planci larval development in the laboratory (0.4 pg Chl a liter-l), there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Field culturing experiments with Acanthasterplanci larvae found that larvae survived well and d e v e l o~e d at near-maximal rates at phytoplankton levels previously believed to be below the minimum threshold for this species (Olson 1987). The use of non-phytoplanktonic food sources, including bacteria, was proposed as a possible explanation for these results, which suggest that starvation may not be an important cause of mortality in A. planci larvae.…”
Section: Ecological Implicationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Field culturing experiments with Acanthasterplanci larvae found that larvae survived well and d e v e l o~e d at near-maximal rates at phytoplankton levels previously believed to be below the minimum threshold for this species (Olson 1987). The use of non-phytoplanktonic food sources, including bacteria, was proposed as a possible explanation for these results, which suggest that starvation may not be an important cause of mortality in A. planci larvae.…”
Section: Ecological Implicationsmentioning
confidence: 91%
“…Since planktotrophic larvae in many regions may encounter phytoplankton abundances that are insufficient to sustain survival and growth, bacteria have been suggested as a supplementary source of organic matter (Crisp et al 1985, Rivkin et al 1986, Olson 1987, Douillet & Langdon 1993 and nutrients (Phillips 1984, Baldwin & Newel1 1995. This hypothesis is supported by studies showing that bivalve larvae can obtain enough energy through bacterivory to meet a portion of a larva's metabolic needs (Chalermwat et al 1991, Douillet 1993b, and that growth and survival are enhanced when certain strains of bacteria are added to phytoplankton cultures used to feed larvae (Martin & Mengus 1977, Douillet & Langdon 1993.…”
Section: Introductionmentioning
confidence: 99%
“…The time that larvae spend in the plankton, or planktonic larval duration (PLD), is constrained by the minimum pre-competency period, which is the necessary time for larvae to complete development before being capable of settling, and the maximum competency period, which is maximum time that larvae can spend in the plankton and still be capable of effective settlement [27]. The minimum time taken for CoTS to develop into late-stage brachiolaria larvae, which are assumed to be competent to settle, is just 9 days [80], though actual settlement has never been documented <14 days post-fertilization [46]. At the other end of the spectrum, Pratchett et al [27] recorded settlement among larvae of A. cf.…”
Section: Question 2 (Larvae Andmentioning
confidence: 99%
“…Corals, the majority of which are broadcast spawners, have a planktonic larval period of generally 2 to 6 wk (Harrison et al 1984); even those which brood their progeny may have larval lives of a s long a s 2 to 3 wk (Fadallah 1983). While data for other coral reef species are relatively few, it appears that the larvae of fish and those of echinoderms (particularly asteroids) spend 2 to 12 wk (Sale 1980, Munro & Williams 1985, and 2 to 4 wk (Yamaguchi 1973, 1977, Olson 1987 respectively in the plankton.…”
Section: Processes Causing Particle Retentionmentioning
confidence: 99%